Accessibility of genitourinary medicine clinics. Issue 1 (February 1996) - Hope, V D; MacArthur, C
Abstract : OBJECTIVES: to examine and compare the accessibility and acceptability of a range of genitourinary medicine (GUM) clinics. DESIGN: five GUM clinics representing different types of locations in the West Midlands Region were selected. All patients attending over the sampling period were included, with data collected by anonymous self completed questionnaire. RESULTS: 297 completed questionnaires were obtained from 360 attendees; 87.4% of attendees had taken 30 minutes or less to get to the clinic, and 66% had used public transport, with variations found between locations. The majority (72.5%) of attendees visited the clinics during their preferred part of the day. Examination of narrower time preferences showed that those wanting to visit in the evening were less likely to be seen during their preferred time than those wanting daytime visits (32% compared with 90%). Of the attendees 98.6% found clinic staff to be friendly and 97.5% did not feel they were being judged because of their sexual activities. The most common reasons for choosing a clinic were recommendation (38.2%) and proximity (36.4%). CONCLUSIONS: the clinics were generally found to be physically accessible, although clinic opening hours need to be reconsidered. Further work is needed on the acceptability of the service in relation to expectations.